43.8k views
4 votes
Explain how to determine the zeros of f(x)=(x+3)(x-1)(x-8)

Explain how to determine the zeros of f(x)=(x+3)(x-1)(x-8)-example-1

2 Answers

5 votes

Answer:

x=-3, x=1, x=8

Explanation:

When you have to find the zero of an equation like (x+3) all you have to do is solve for x.

x+3=0 equal the equation to zero

x+3-3=0-3 cancel out 3

x=-3 answer


If you have to find the zero of an equation like f(x)=-2x^2 - 5x + 7 then you would have to factor the equation.

7*-2=-14 multiply

-7 & 2 find the two numbers that when multiplied =14 and when added = -5

(2x^2 + 2) (-7x + 7) replace -5 with -7 & 2

-2x (x - 1) -7 (x - 1) factor

(x - 1) (-2x - 7) rewrite

1st: x - 1 = 0

x = 1 : Answer

2nd: -2x - 7= 0

-2x - 7 + 7 = 0 + 7

-2x = 7

-2x / -2 = 7 / -2

x = 7 / -2 : Answer





5 votes

Answer:

Solution : x = -3, x = 1 , x = 8,

Steps : 1) Set f ( x ) = 0.

2) Set each factor equal to zero and solve to find the x- intercepts.

Explanation:

Given : f(x)=(x+3)(x-1)(x-8).

To find : how to determine the zeros .

Solution : We have given that : f(x)=(x+3)(x-1)(x-8).

Steps for finding zeros

1) Set f ( x ) = 0.

2) Set each factor equal to zero and solve to find the x- intercepts.

Set f(x) = 0

(x+3)(x-1)(x-8) = 0

Now each factor equal to zero

(x+3) = 0

On subtracting by 3 both sides

x = -3

(x-1) = 0

On adding by 1 both side.

x = 1.

(x-8) = 0.

On adding by 8 both side.

x = 8.

Therefore, Solution : x = -3, x = 1 , x = 8,

Steps : 1) Set f ( x ) = 0.

2) Set each factor equal to zero and solve to find the x- intercepts.

User Shubham Arora
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.